PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KEMAMPUAN MANAJERIAL TERHADAP KINERJA GURU (Studi Pada Guru SMP Negeri 6 Kaimana Kabupaten Kaimana) - Subijanto; Fatimah Riswati; Arlyns (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
The Purpose of study are 1). Describe the Principal leadership, managerial abilities and the performance of teachers of SMP Negeri 6 Kaimana, Kaimana Regency. 2) Find out and test whether the principal's leadership and managerial abilities have a simultaneous and significant influence on the performance of teachers of SMP Negeri 6 Kaimana, Kaimana Regency. 3) Find out and test whether the principal's leadership and managerial abilities have a partial and significant influence on the performance of the teachers of SMP Negeri 6 Kaimana, Kaimana Regency. 4.) Find out and test which variables between the principal's leadership and managerial abilities have a dominant influence on the performance of teachers at SMP Negeri 6 Kaimana, Kaimana Regency. This type of research is expalanotory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 36 employees. The results showed that: 1). The leadership of the Principal (X1) has a positive and significant effect on the improvement of the teacher performance of SMP Negeri 6 Kaimana Kaimana Regency, it is proven to be true and the hypothesis is accepted. 2). Managerial ability (X2) has a positive and significant effect on improving the performance of teachers at SMP Negeri 6 Kaimana, Kaimana Regency, it is proven and the hypothesis is accepted.